Lời giải:
a)
$\widehat{xOy}+\widehat{yOz}=150^0$
$\widehat{xOy}-\widehat{yOz}=90^0$
$\Rightarrow \widehat{xOy}=(150^0+90^0):2=120^0$
$\widehat{yOz}=(150^0-90^0):2=30^0$
b.
$\widehat{xOz}=\widehat{xOy}+\widehat{yOz}=150^0$
$\widehat{yOz'}=180^0-\widehat{yOz}=180^0-30^0=150^0$
Do đó $\widehat{xOz}=\widehat{yOz'}$
a) Ta có: \(\widehat{xOy}+\widehat{yOz}=150^0\)
\(\widehat{xOy}-\widehat{yOz}=90^0\)
Do đó: \(2\cdot\widehat{xOy}=150^0+90^0=240^0\)
hay \(\widehat{xOy}=120^0\)
Ta có: \(\widehat{xOy}+\widehat{yOz}=150^0\)
nên \(\widehat{yOz}=30^0\)